The Role Of Walking Activities On The Level Of Dysmenorrhea In Young Girls At Smp Negeri 1 Bondowoso. - Grido Handoko Sriyono; Nur Hamim; Umi Narsih (Al-Makki Publisher, 2022)
Menstruation is one of the early characteristic changes in adolescents. Dysmenorrhea has a considerable impact on adolescents. Lack of physical activity will reduce the distribution of oxygen in the systemic circulation, thereby increasing a person's perception of pain, including dysmenorrhea. The purpose of this study was to analyze the effectiveness of walking with the level of menstrual pain (dysmenorrhea) in adolescent girls at SMP Negeri 1 Maesan Bondowoso. The design of this research is experimental research with One-Group Pretest-Posttest Design. The population in this study were students in grades 7 and 8 at SMP Negeri 1 Maesan Bondowoso who had a history of menstrual pain of 30 people. The sample size in this study was 30 people who were taken randomly. Collecting data using a questionnaire then the data is processed using SPSS using the Mann-Whitney U Test. The results of data analysis showed that before physical activity, most of the pain was mild as many as 18 people (60%) and after physical activity, most of the pain was mild as much as 19 people (63.3%). Sig) of 0.000 <0.05, meaning that ho is rejected and ha is accepted, so that walking is effective against the level of menstrual pain (dysmenorrhea) in adolescent girls at SMP Negeri 1 Maesan Bondowoso. The hypothesis in this study is accepted and statistically proven. It is recommended that adolescents increase physical activity at home and at school such as jogging, walking etc.